English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

P(x)=x^3-4x^2-7x+10

2006-11-08 11:41:42 · 4 answers · asked by jere 1 in Science & Mathematics Mathematics

4 answers

Well, by inspection -2 is one root...

P(-2) = (-2)^3 - 4(-2)^2 - 7(-2) + 10
P(-2) = -8 - 16 + 14 + 10
P(-2) = -24 + 24
P(-2) = 0

Now take your equation and divide by (x - (-2)). In other words (x + 2):

............ 1 -6 5
1 2 ) 1 -4 -7 10
....... 1 2
....... ---------
........... -6 -7
........... -6 -12
........... ----------
............... 5 10
............... 5 10
............... ------
.................... 0

So the result is x^2 - 6x + 5

This can be factored to (x - 5)(x - 1)

This results in (x + 2)(x - 5)(x - 1)

And your roots are:
-2, 5, 1

(I don't know why I didn't notice 1 as a root... I usually check that first...)

2006-11-08 11:47:23 · answer #1 · answered by Puzzling 7 · 4 4

-by inspection try x=1:
since P(1) = 0 that means x-1 is a factor.
-divide P(x) by (x-1)
(x^3 -4x^2 -7x +10)/(x-1) = x^2 -3x - 10
-you can factor x^2 -3x -10 into (x-5)(x+2)
-therefore, your zeros are 1, 5 and -2

2006-11-09 15:08:27 · answer #2 · answered by locuaz 7 · 1 0

Tip 1:
If the sum of the coeffictients of a polymer is zero then 1 is one of the zeros.

Tip 2:
If there are rational roots and the first coefficient of the polynom is 1, then the roots are all the divisors of the last coefficient.

So normally you will use Tip2 and try those roots (1,2,5,10 and the negatives). In this case use tip 1. do the synthetic division and solve by the quadratic formula.

x1 = 1
P(x) = (x -1)*(x^2 -3x - 10)
x2 = 5
x3 = -2
P(x) = (x - 1) * (x - 5) * (x + 2)

2006-11-08 19:58:13 · answer #3 · answered by Dr. J. 6 · 2 1

Start by listing all the possible rational zeros.
They are the factors of 10.
-1, 1, -2, 2, -5, 5, -10, 10
Now pick one until you find one that gives you P(x) = 0
Try x = 1
P(1) = 1^3 - 4(1^2) - 7(1) + 10
P(1) = 1 - 4 - 7 + 10 = 0
Since P(1) = 0 that means x-1 is a factor.
Divide P(x) by (x-1)
(x^3 -4x^2 -7x +10)/(x-1) = x^2 -3x - 10
You can factor x^2 -3x -10 into (x-5)(x+2)
Therefore, your zeros are 1, 5 and -2

2006-11-08 19:45:19 · answer #4 · answered by MsMath 7 · 5 6

fedest.com, questions and answers